L'atelier de potier archïque de Phari (Thasos) : la production de tuiles - Perreault, Jacques Y. (Hesperia: The Journal of the American School of Classical Studies at Athens, 1990)
The roof tiles and covering joints of Laconian type discovered in an ancient workshop at Thasos between 1985 and 1988 can most likely be dated between the last quarter of the 6th cent. B.C. and the first quarter of the 5th cent. The presence of vase fragments at the site raises the possibility that both tiles and vases were produced in the same shop – an apparent rarity for this period.